Nickel-Chitosan Hybrid as a Precursor for Nickel Oxide Nanoporous Particles for Organic Dyes Photodegredation - F. Farzaneh (Journal of Sciences, Islamic Republic of Iran)
Hydrothermal synthesis of nickel-chitosan hybrid  has  been accomplished using Ni(CH3COO)2,4H2O, chitosan and water as starting material, template and solvent respectively, followed by calcination at 800 and 900˚C to provide nanoporous NiO800  and NiO900. The solid products were characterized by X-ray diffraction (XRD), nitrogen adsorption-desorption, scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) techniques.  NiO800 proved to be active for adsorption of Congo red with pseudo-second order kinetic model and adsorption isotherms, respectively fitted by Freundlich equation. NiO900 was also found to successfully catalyze the photodegradation of organic dye pollutants such as Congo red  and methylene blue. The kinetic of photocatalytic behavior of NiO900 have proven to obey the first order and Langmuir–Hinshelwood model.